Clinical predictive factors of long‐term survival after curative resection of pancreatic cancer: a retrospective study. (18th September 2017) - Nakano, Yutaka; Kitago, Minoru; Shinoda, Masahiro; Abe, Yuta; Yagi, Hiroshi; Hibi, Taizo; Takeuchi, Ayano; Aiura, Koichi; Itano, Osamu; Kitagawa, Yuko
Abstract: Pancreatic ductal adenocarcinoma (PDAC) continues to have the poorest prognosis of all gastrointestinal malignancies, even after the tumor has been completely resected. However, only a proportion of patients achieve 5‐year survival after resection. The factors predictive of achieving 5‐year survival remain unclear. The aim of this study was to investigate the pre‐ and postoperative clinicopathological characteristics of PDAC patients with a >5‐year survival after curative resection. We retrospectively reviewed patients who underwent pancreatectomy for PDAC between January 1995 and December 2011. Logistic regression analysis was performed to determine the predictive factors for 5‐year survival. One hundred and fifty‐one patients were enrolled, including 38 patients with 5‐year survival (actual 5‐year survival rate, 25.2%). The independent preoperative factors predictive of achieving 5‐year survival included serum albumin levels (odds ratio [OR]: 5.06, 95.0% confidence interval [CI]: 1.49–17.19; P  =   0.009) and neoadjuvant chemoradiotherapy (OR: 3.02, 95.0% CI: 1.00–9.08; P  =   0.049). Venous infiltration (OR: 2.99, 95.0% CI: 1.09–8.25; P  =   0.034), liver recurrence (OR: 0.17, 95.0% CI: 0.04–0.69; P  =   0.013), and perioperative portal vein infusion chemotherapy (OR: 3.06, 95.0% CI: 1.09–8.25; P  =   0.028) were found to be independent postoperative predictive factors for achieving 5‐year survival. Serum albumin levels could be a biomarker for predicting the prognosis of PDAC patients after curative resection. Liver recurrence and perioperative portal vein infusion chemotherapy were independent postoperative factors, suggesting that perioperative portal vein infusion chemotherapy could be promising for improving the survival rate of PDAC patients after curative resection. Abstract : Relationship between neoadjuvant chemoradiotherapy (NACRT) and (A) postoperative disease‐free survival (DFS) and (B) postoperative overall survival (OS) and relationship between perioperative adjuvant portal vein infusion (PVI) chemotherapy and (C) postoperative DFS and (D) postoperative OS.